SLANTLET TRANSFORM-BASED OFDM SCHEME (Journal of Engineering, 2006)
Wireless digital communication is rapidly expanding resulting in a demand for systems that are reliable and have a high spectral efficiency. To fulfill these demands OFDM technology has drawn a lot of attention. In this paper a new technique is proposed to improve the performance of OFDM. The new technique is use the slantlet transform (SLT) instead Fast Fourier transform (FFT) in order to reduce the level of interference. This also will remove the need for Guard interval (GI) in the case of the FFT-OFDM and therefore improve the bandwidth efficiency of the OFDM. The SLT-OFDM is also better than wavelet packet (WP)-OFDM in the selective channel because the slantlet filter bank is less frequency selective than the traditional DWT filter bank, due to the shorter length of the filters and SLT algorithm is faster than WP algorithm. The main results obtained indicate that the performance of SLT-OFDM is better on average by 18dB in comparison with that of FFT-OFDM flat fading channels. For frequency selective fading channel the SLT-OFDM performs is better than the FFT-OFDM on the lower SNR region, while the situation will reverse with increase SNR values.